2016
DOI: 10.1136/jmedgenet-2016-103756
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biallelicLRRK1mutations in osteosclerotic metaphyseal dysplasia and evidence for locus heterogeneity

Abstract: Background Osteosclerotic metaphyseal dysplasia (OSMD) is a unique form of osteopetrosis characterised by severe osteosclerosis localised to the bone ends. The mode of inheritance is autosomal recessive. Its genetic basis is not known. Objective To identify the disease gene for OSMD. Methods and results By whole exome sequencing in a boy with OSMD, we identified a homozygous 7 bp deletion (c.5938_5944delGAGTGGT) in the LRRK1 gene. His skeletal phenotype recapitulated that seen in the Lrrk1-deficient mouse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 22 publications
2
66
0
1
Order By: Relevance
“…In addition, Lrrk1 KO mice responded normally to PTH anabolic treatments but were resistant to ovariectomy-induced bone loss. Consistent with our observations in the Lrrk1 KO mouse model, our recent human genetic studies have identified a severe osteopetrosis phenotype at the vertebra and the metaphysis of long and short tubular bones in a patient with Lrrk1 deletion and frame-shifted mutation (15). These observations make Lrrk1 an attractive antiresorptive drug target because Lrrk1 KO mice have normal membranous bone, and inhibiting Lrrk1 may not interfere with osteoclast-coupled bone formation in the maxilla and mandible or cause osteonecrosis of the jaw.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In addition, Lrrk1 KO mice responded normally to PTH anabolic treatments but were resistant to ovariectomy-induced bone loss. Consistent with our observations in the Lrrk1 KO mouse model, our recent human genetic studies have identified a severe osteopetrosis phenotype at the vertebra and the metaphysis of long and short tubular bones in a patient with Lrrk1 deletion and frame-shifted mutation (15). These observations make Lrrk1 an attractive antiresorptive drug target because Lrrk1 KO mice have normal membranous bone, and inhibiting Lrrk1 may not interfere with osteoclast-coupled bone formation in the maxilla and mandible or cause osteonecrosis of the jaw.…”
supporting
confidence: 91%
“…Previous findings of the dramatic reduction in bone resorption and the persistent resistance to ovariectomy-induced bone loss in the Lrrk1 KO mice (36) and the recent identification of an osteosclerotic patient with an autosomal recessive mutation of Lrrk1 (15) provide unequivocal evidence that Lrrk1 plays a critical role in regulation of bone homeostasis. Mice with disruption of Lrrk1 exhibited severe osteopetrosis phenotypes in the femurs, tibias, and vertebrae due to dysfunction of mature osteoclasts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lrrk1 KO mice have normal teeth, are healthy through one year of age and respond to anabolic PTH treatment, but are resistant to ovariectomy-induced bone loss (9) . More recently, mutations in LRRK1 gene have been identified in human patients (10) . The clinical features of affected patients resulting from the dysfunction of Lrrk1 in OC were very similar to the skeletal phenotypes observed in the Lrrk1 KO mice (9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, mutations in LRRK1 gene have been identified in human patients (10) . The clinical features of affected patients resulting from the dysfunction of Lrrk1 in OC were very similar to the skeletal phenotypes observed in the Lrrk1 KO mice (9,10) . These studies suggest that Lrrk1 could be an antagonist drug target for treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%